(3QSGdI aj EKHGJ GdUGfYs - (3GdTQhGfj, GdCUagGfj, GdeTgOj, eMeO Hf GdMSf, J (B1098(3g`s
(3ChdgG (B:s
(3ebUhO GdcJGH(B... (3aj PcQ eG JbQQ dOjfG aj EKHGJ gPG (B... (3ChdG HCf hLhO GdTjA aj faSg djS MbjbI(B...s
(3BNQgG (B:s
(3hGdLhGH Cf GdcdGe CRdj dcf JYdbGJg HGdCTNGU hGdCReGf MGOKI(B. (3JeJ GdQSGdIs
(3JHUQI GdeDda (B:s
(3hjbGd(B: (3GdTjQhGfj, HEVGaI jGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B221s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B300s
(3GdPQjYI; HQbe(B: 523s
Keywords: (3GdJhMjO hGdedd hGdfMds